GEOTHERMIC FIELD AND DEVELOPMENT OF THE STRUCTURE OF CONTINENTS - Beloussov V.V. (My University, 1985)
Tectonic, magmatic and metamorphic processes combine into endogenous regimes. There is direct correlation between the degree of excitation of endogenous regimes and observed heat flow. There are grounds to suppose that all varieties of endogenous regimes, their distribution and their history depend on the heterogeneity in space and time of the Earth's thermal field.